PENGABDIAN MASYARAKAT MELALUI KKN: MENINGKATKAN PERAN IBU DAN KELUARGA DALAM PENDIDIKAN DAN POLA ASUH ANAK DI DESA WONOPRINGGO - Rizal Bilhakiki; Evva Aini; Akhmad Aufa Syukron; Titania Candra; Satria Dwi Santoso (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2026)
There are several aspects of parenting that relate to how parents nurture and guide their children. When parents can psychologically understand their children's behavior and intentions, children automatically adopt good communication relationships to have social interactions around them. The method used in this research is a qualitative method with a case study approach. Community service through KKN conducted by UIN KH Abdurrahman Wahid students in Wonopringgo Village in the form of parenting socialization to Dharma Wanita Kindergarten student guardians aims to increase parents' knowledge about good parenting. The discussion of the results of parenting counseling or socialization to kindergarten student guardians will focus on four main aspects: (1) Increased parenting knowledge of Dharma Wanita Kindergarten student guardians; (2) Changes in parents' attitudes towards children's education; (3) Application of effective parenting techniques; (4) Social support from the environment. Based on the above discussion, it can be concluded that parenting is very important and affects the formation of a child's personality after he or she becomes an adult.